STEADY-STATE MODELLING OF BIOGEOCHEMICAL PROCESSES IN COLUMNS WITH AQUIFER MATERIAL: - 2. DYNAMICS OF IRON-SULFUR INTERACTIONS - von Gunten U.; Furrer G. (My University, 2000)
Serial data from column experiments were used to develop a dynamic model to describe the evolution of concentration profiles of redox-sensitive chemical components such as iron(II), sulfate/sulfide, FeOOH(s), and FeS(s). The experimental results were gained from a study with a laboratory column filled with aquifer sand and operated in a water-saturated state. ''Reduction of sulfate'', ''reduction of FeOOH(s)'', ''formation of FeS(s)'' and ''precipitation of FeS(s)'' were identified as slow nonequilibrium reactions. The rate coefficients of these processes were determined by using an extended version of the program STEADYQL in combination with the parameter optimisation program SUFI. Based on this kinetic information it is possible to carry out prognostic modelling of the propagation of a sulfide plume in an anaerobic aquifer if the main characteristics of the solids' surfaces are known.The major sink for sulfide turned out to be FeOOH(s) that is gradually transformed into FeS(s). The Ti(III)EDTA-extractable fraction of FeOOH(s) appeared to be a good measure for the overall sulfide-immobilisation capacity. Under the prevailing experimental conditions with a flow velocity of approximately 1 m/day and a dissolved sulfate concentration in the inflow of 215 μM, the calculated sulfide front migrates in the order of 1 m/year. These model findings indicate that even in aquifers, where strongly reducible conditions are predominant, sulfide immobilisation by iron may lead to a sulfide-free groundwater for a long period.
Keywords: REDOX; AQUIFER; GROUNDWATER; SULFUR; IRON; MODELLING